Erratum: Catalytic studies of animated MCM-41-tethered rhodium complexes for hydroformylation of 1-octene and styrene (Journal of Molecular Catalysis A: Chemical (2004) 213 (241-249) DOI: 10.1016/j.molcata.2003.12.007) - Huang, L. (2014)
10.1016/j.molcata.2004.06.001